Characterization of the SPARC4 CCDs. (19th July 2018) - Bernardes, D V; Martioli, E; Rodrigues, C V
Abstract: We present the photometric characterization of the four iXon Ultra 888 CCD cameras of the SPARC4 instrument, which will be installed on the 1.6 m telescope of the Pico dos Dias Observatory in Brazil. We applied experimental methodologies for a systematic characterization of the read noise, electronic gain, dark current, and quantum efficiency of the CCDs. We have analyzed the statistical distribution of the read noise, and also its spatial gradient and temporal variability, where we obtained an average value of the read noise of 6.33 electrons. We applied the Janesick method to determine the electronic gain, where we obtained an average value of 3.35 e-/ADU. We have also obtained an average dark current of 0.00014 e- pix −1 s −1 for CCD internal temperature of −70 °C. We have inspected the dependency of the dark current with temperature and the spatial distribution of the dark current, where we found a variable profile in the CCD 9917. We developed an experiment using a bench-mounted monochromator to obtain the spectral dependency of the quantum efficiency in the spectral range between 350 nm and 1100 nm, where we measured the quantum efficiency for each camera. The camera 9915 presents the highest quantum efficiency of 95.8%. Our results are compared with those from the manufacturer. These experiments allow us to diagnose the performance of these CCD cameras, an important sub-system of the SPARC4 instrument. It also provides a systematic way for monitoring the aging of the CCDs.